Decorative renders simulating stone of middle 20th century in the region of Lisbon - Veiga, Rosário (2020)
Housing and public urban buildings of the middle 20th century period, in Portugal, are characterized by a sober, rather severe, architectural and constructive design, known as “Estado Novo” period. In the region of Lisbon, the façades of many of those buildings are covered with a very durable unpainted decorative type of render, called “marmorite”. Considering that cementitious binders were already often used in that period, both in structural elements and in coatings, and due to the darkening effect of fungus, soiling and pollution, there was a generalized belief that marmorite renders were cement-based mortars. As a consequence, repair interventions used materials and techniques chosen for cementitious renders. However, the characterization of the marmorite render of the National Laboratory for Civil Engineering main building, in Lisbon, revealed that the render was composed by air lime, limestone and marble. Later, an experimental characterization campaign of samples of marmorite renders of 20 other buildings in the region of Lisbon revealed that they were generally composed by air lime, sometimes coloured with an inorganic pigment, and mainly limestone and marble aggregates of different colours selected to obtain an aesthetic effect.